Pituitary apoplexy and associated cranial nerve palsies secondary to bleeding caused by immune thrombocytopaenia in a patient with known pituitary macroadenoma. Issue 5 (31st May 2021) - Ambrose, Christopher; Sarma, Sruthi; Banerjee, Ritwick; Myers, Sam
Abstract : An 84-year-old man presented with a frontal headache and easy bruising. He had a background history of a pituitary macroadenoma, diagnosed incidentally a year earlier. Investigations showed haemorrhage into the pituitary macroadenoma leading to a diagnosis of pituitary apoplexy in the context of low platelet count secondary to immune thrombocytopaenia. He was treated with intravenous hydrocortisone, platelet transfusion, intravenous immunoglobulin and high-dose steroid. Neurosurgical intervention was not indicated initially. Five days into his admission, he developed bilateral ptosis and ophthalmoplegia. MRI confirmed further haemorrhage associated with compression of the optic chiasm. He was transferred to a tertiary neurosurgical centre where he underwent urgent surgical decompression. To date, there has been minor improvement in his neurological symptoms. Management of this patient required considerable multidisciplinary teamwork between the clinics of endocrinology, haematology, neurosurgery, ophthalmology and geriatrics.